Ceapins inhibit ATF6α signaling by selectively preventing transport of ATF6α to the Golgi apparatus during ER stress - Ciara M Gallagher; Peter Walter (eLife, 2016)
The membrane-bound transcription factor ATF6α is activated by proteolysis during endoplasmic reticulum (ER) stress. ATF6α target genes encode foldases, chaperones, and lipid biosynthesis enzymes that increase protein-folding capacity in response to demand. The off-state of ATF6α is maintained by its spatial separation in the ER from Golgi-resident proteases that activate it. ER stress induces trafficking of ATF6α. We discovered Ceapins, a class of pyrazole amides, as selective inhibitors of ATF6α signaling that do not inhibit the Golgi proteases or other UPR branches. We show that Ceapins block ATF6α signaling by trapping it in ER-resident foci that are excluded from ER exit sites. Removing the requirement for trafficking by pharmacological elimination of the spatial separation of the ER and Golgi apparatus restored cleavage of ATF6α in the presence of Ceapins. Washout of Ceapins resensitized ATF6α to ER stress. These results suggest that trafficking of ATF6α is regulated by its oligomeric state.